Women, work, and wage equity in agricultural labour in Saiss, Morocco. Issue 4 (19th May 2018) - Najjar, Dina; Baruah, Bipasha; Aw-Hassan, Aden; Bentaibi, Abderrahim; Kassie, Girma Tesfahun
ABSTRACT: This article documents wages and working conditions for landless female and male agricultural labourers in Morocco. We found that higher-paid, equipment-intensive tasks were predominantly assigned to men, whereas women often performed lower-paid, time-intensive tasks. Women were systematically paid less than men even when they performed the same tasks. Enforcing existing legislation in Morocco to ensure equal pay for women is an essential first step towards enabling women to benefit equitably with men from their agricultural labour contributions. A revalorisation of the importance of agriculture is also necessary so that agricultural labour is not perceived as an occupation of last resort.